Assessing computational thinking in libraries. Issue 2 (3rd April 2021) - Weintrop, David; Morehouse, Shandra; Subramaniam, Mega
ABSTRACT: Background and Context : Computational thinking (CT) is an essential skill for all youth to succeed in our technology and information-rich world. While CT has a growing presence within K-12 classrooms, libraries play an essential role in introducing these critical skills to all. Objective : Assessing learning in libraries is difficult given their informal nature. This is especially true when trying to assess a new and ill-defined construct like CT. A first step towards better supporting informal educators is to identify the motivations for bringing CT into informal spaces and to understand the current state of assessing CT in public libraries. Method : Thirty-seven interviews with library staff from across the United States were conducted and analyzed. Findings : This work reveals the variety of motivations justifying the inclusion of CT programming for youth in libraries, the challenges associated with assessing CT in libraries, and identifies the assessments library staff would like to be able to conduct for their own CT-related programming. Implications : This work advances our understanding of the current state of CT assessment in public libraries and lays the groundwork for future work seeking to meet the needs of those tasked with bringing CT to youth beyond the classroom.